Cat–Human Intersubjectivity and Joint Meaning-Making within Multispecies Families and Communities - Hill, Kristine (Humanimalia, 2024)
This paper examines unstructured interview transcripts from case-studies of cat-human relationships, using the framework of interspecies intersubjectivity. Adopting a qualitative thematic approach, this study explores how interspecies relationships are formed and performed within the context of multispecies families and communities. Themes emerged relating to how the cats in this study became integrated into multispecies families and communities, through mutual trust-building, interspecies communication, and joint meaning-making. Examples of co-creation of meaning within the cat-human relationships included special vocalizations or signals with shared meaning that were co-developed over time. All the cats exerted their agency in some manner that influenced human behaviour. Most notably, by convincing their guardian to let them out to roam and to trust them. Although undoubtably influenced by their kittenhood experiences, individual personalities rendered some cats inherently more eager to roam and others more content to stay home. This study highlights several friendships formed between cats and nonguardian humans and provides insight into how cats integrate themselves into their communities. Furthermore, it demonstrates how cats are proactive in the process of becoming members of multispecies families.